The Islam and Insurance In Indonesia - Mu'adil Faizin (Postgraduate State Islamic Institute (IAIN) Metro, 2017)
The development of Islamic business thinking encourages a variety of sharia-based business practices, Sharia Insurance, meeting the two variables